Prevalence and Determinants of Malnutrition Among Children Under Five in Ethiopia: Ethiopian Mini Demographic Health Survey (EMDHS) 2019 - Degu, Dawit Ayenew; Hasanbasri, Mubasysyir; Arjuna, Tony (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to assess the prevalence and determinants of malnutrition among children under five in Ethiopia, with evidence from the 2019 Ethiopian demographic and health survey as evidence. Methods: The data were analyzed from the 2019 EMDHS, and 3680 (939 urban and 2,741 rural) children under 5 years old were considered in this analysis. The data was extracted, edited, and analyzed using SPSS Version 26. Binary logistic regression models were used to identify the determinants of children's malnutrition. Results: The prevalence of stunting, wasting, and underweight was 31.7%, 9.4%, and 17%, respectively. About 24.5% of children were both stunted and wasted. Among the factors considered in this study, residence region, breastfeeding, electricity, mothers’ education level, household wealth index, child sex, and water and toilet facilities were significantly associated with under-five malnutrition in Ethiopia. Conclusion: Malnutrition among under-five children is one of Ethiopia's public health problems. Therefore, the influence of these factors should be considered in developing an evidence-based health policy and implementing interventions in the healthcare system that target stunting, wasting, and underweight, which can lead to better outcomes for children under five in Ethiopia.